2006
DOI: 10.1016/j.marpolbul.2005.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Liver histopathology in Baltic flounder (Platichthys flesus) as indicator of biological effects of contaminants

Abstract: Results are presented of a study on liver histopathology in Baltic flounder (Platichthys flesus) carried out in 2001 and 2002 in four coastal sampling areas of the Baltic Sea: Kvädö fjärden (Swedish east coast, reference area), Klaipeda-Butinge (Lithuanian coast), Gulf of Gdansk (Polish coast), and Wismar Bay (German coast) within the framework of the EU-funded BEEP project. Liver lesions were diagnosed and categorised using standardised methodologies and, for a spatial and temporal assessment of the prevalenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
41
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 33 publications
(39 reference statements)
3
41
1
1
Order By: Relevance
“…Existing long-term data on external visible diseases for flounder from the southern Baltic could provide links to population health. The data presented by Lang et al (2006) on liver histopathology indicated that flounder specimens from the Gulf of Gdansk were significantly less affected by any kind of lesion than flounder from Kvädöfjärden and from the Lithuanian coast.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Existing long-term data on external visible diseases for flounder from the southern Baltic could provide links to population health. The data presented by Lang et al (2006) on liver histopathology indicated that flounder specimens from the Gulf of Gdansk were significantly less affected by any kind of lesion than flounder from Kvädöfjärden and from the Lithuanian coast.…”
Section: Discussionmentioning
confidence: 94%
“…PCBs, DDTs) have been reduced over the past 20-30 years, chemical pollution by a wide spectrum of hazardous substances may be assumed to be higher today than ever before. The results of pan-European project BEEP (Biological Effects of Environmental Pollution on Marine Coastal Ecosystems, 2001Ecosystems, -2004 clearly indicated that present contaminant concentrations in different zones of the Baltic Sea are eliciting biological responses in various species, in some cases are leading to chronic stress and neoplastic lesions (Baršien_ e et al 2006a, b;Kopecka et al 2006;Lang et al 2006;Schiedek et al 2006;Vuorinen et al 2006). The majority of the available literature data (especially concerning contamination with POPs and trace metals) indicates that the Gulf of Gdansk is a polluted region (Biziuk et al 2001;Perttilä et al 2003;Pazdro 2004).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, catfish are more likely to be exposed to higher concentrations of potential contaminants through biomagnification. Previous studies has shown that the liver can be a useful biomarker of toxicant exposure (Schlacher et al, 2007;Lang et al, 2006;Nero et al, 2006;Feist et al, 2004;Au, 2004;Stentiford et al, 2003;Wester et al, 2002;Schmidt-Posthaus et al, 2001;Schmidt et al, 1999;Swee et al, 1996;Braunbeck and Völkl, 1993;Hinton et al, 1992). The results therefore provide valuable liver baseline data for future monitoring programmes in the RD.…”
Section: Discussionmentioning
confidence: 99%
“…Field studies in the framework of the EU-funded BEEP project (Biological Effects of Environmental Pollution in Marine Coastal Ecosystems, 2001Ecosystems, -2004) demonstrated biological impacts of pollution in different coastal areas of the Baltic Sea and the North Sea Baršienė et al, 2004Baršienė et al, , 2006bBaršienė et al, , 2006dLang et al, 2006;Schiedek et al, 2006;Kopecka et al, 2006). Highest genotoxicity levels were observed in fish and mussels from the Gulf of Gdansk.…”
Section: Discussionmentioning
confidence: 99%